(untitled) - Bartlett, Bruce (Boston, 2002)
Practical Recording Techniques, Third Edition is a hands-on, practical guide for beginning and intermediate recording engineers, producers, musicians, and audio enthusiasts, offering guidance on a variety of recording situations, including small profesional studios and on-location recording for both popular and classical music. It gives advice on equipping a home studio-from low-budget to advanced-and inclides suggestions for set-up, acoustics, choosing monitor speakers, and preventing hum.
Keywords: Magnetic recorders and recording,Sound; Handbooks, manuals, etc.,Recording and reproducing,Handbooks, manuals, etc